The effect of different chelating agents on the push-out bond strength of proroot mta and endosequence root repair material - Arife Kaptan; Fatih Öznurhan; Burak Buldur (Istanbul University, 2019)
Purpose This study aimed to evaluate the effects of 17% ethylenediaminetetraacetic acid (EDTA), 7% maleic acid (MA), and 10% citric acid (CA) on the push-out bond strength of ProRooT MTA and Endosequence Root Repair Material (ERRM) putty. Materials and Methods Eighty single-rooted extracted human teeth were instrumented to obtain a standardized immature teeth model. Based on the chelating agents tested, the specimens were randomly divided into three experimental groups: Group 1 (17% EDTA), Group 2 (7% MA), Group 3 (10% CA), and Group 4 (Positive Control) (n=20 for each group). Each group was further classified into two subgroups: Group A (ProRoot MTA) and Group B (Endosequence Root Repair Material (ERRM) putty) (n=10 for each subgroup). After irrigation and placement of cements, teeth were stored at 37°C and in 100% humidity for a week. A total of 240 dentine discs (three discs per teeth) were obtained and subjected to push-out assay. Data was analyzed using two-way analysis of variance and Tukey's post hoc t-test. Results Both types of chelating agent and calcium silicate-based cement were significantly associated with the push-out bond strength values. The push-out bond strength was significantly less for CA as compared to EDTA or MA. ERRM had higher bond strength values than ProRoot MTA (p<0.05). Conclusion The use of chelating agents increased the push-out bond strength of CSC. Regardless of tested chelating agents, ERRM had higher bond strength values than ProRoot MTA.